THE ORIGINAL INHABITANTS OF INDIA: VICTIMS OF WRITTEN TRADITIONS: . - Vadakumchery, J. (Journal of Dharma, 1991)
In the 77th Indian Science Congress held at Cochln in February 1990 a question was raised: Can we substitute the term ’tribe/iidiviisi’ with ’dalit’? The argument was that the word ’tribe’ is an administrative invention used by outsiders; ’dalit’ is a more generic term depicting the deplorable conditions of a people who are at the bottom of Indian society